Evaluation of the Long-Term Economic Implications of Deploying Renewable Energy Versus Traditional Energy Sources in a Nigerian University - Fredrick Nnaemeka Okeagu; Chisom Precious Nwajiaku; Franklin Chinemerem Ezedinachi; Ugochukwu Divine Muoghalu (Greenation Research & Yayasan Global Resarch National, 2026)
This study evaluates the cost-benefit of installing a solar power system in the Department of Industrial and Production Engineering, Nnamdi Azikiwe University, Awka, Nigeria. With frequent power outages and the high cost of fuel-based generators, the department faces increasing energy-related expenses and operational challenges. The research garnered data of the current power sources in the department (Grid electricity and generator), and the possible cost of solar power installation. The cost evaluation was done using the Net Present Value (NPV) and Future Value formulars, for a projected period of 25-years. A comparative analysis of the three options was done, results show that the solar system, with a total cost of ₦29.33 million, is far more sustainable compared to grid electricity (₦102.19 million) and generators (₦240.98 million). The analysis confirms that solar power provides significant long-term financial savings, greater reliability, and environmental benefits. It is therefore recommended as the optimal energy solution for the department, serving both academic and practical sustainability goals